Zasłużeni dla miasta. O mikrosystemie plateonimicznym Opola - Wojcieszek, Agnieszka (Nazwy terenowe i miejscowe w przestrzeni fizycznej, 2016)
The Opole urban nomenclature has for many years been a space of special homage paid to the local heroes. Taking into account this fact, in my research I have concentrated on Opole streets, squares, buildings and estates named after persons associated with this region. The analysis covered not only outstanding historical personalities, but also contemporary authorities – writers, politicians and scientists. The purpose of this paper was to present the most important nomenclature trends associated with the regional history and to show the impact of names commemorating prominent historical figures on the contemporary image of Opole. This urban nomenclature microsystem consisting of about one hundred proper names was presented against the background of current events and terminology problems faced by the Opole region. This subject seems to be of importance in the light of the ongoing cultural-ethnic differentiation and political disputes in Opole Silesia.